2012
DOI: 10.1037/h0093923
|View full text |Cite
|
Sign up to set email alerts
|

Sequential lineup presentation promotes less-biased criterion setting but does not improve discriminability.

Abstract: When compared with simultaneous lineup presentation, sequential presentation has been shown to reduce false identifications to a greater extent than it reduces correct identifications. However, there has been much debate about whether this difference in identification performance represents improved discriminability or more conservative responding. In this research, data from 22 experiments that compared sequential and simultaneous lineups were analyzed using a compound signal-detection model, which is specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
130
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(150 citation statements)
references
References 57 publications
18
130
2
Order By: Relevance
“…The analysis reported by Palmer and Brewer (2012) represents an important step forward in that it used signal-detection concepts to clearly separate accuracy-that is, how far an ROC falls above the diagonal line of chance performance-from response biasthat is, where a point falls on an ROC (Ebbesen & Flowe, 2002;Meissner et al, 2005). However, actually performing ROC analysis would be a far better way to investigate this issue because it is not dependent on detailed theoretical assumptions, whereas the analysis reported by Palmer and Brewer is dependent on numerous minimally tested assumptions that eyewitness memory researchers are free to dispute (e.g., the target and lure distributions are assumed to be Gaussian in form and to have the same variance, an integration decision rule is assumed instead of an independent observations decision rule, the decision rule is assumed to be the same for both lineup procedures, etc.).…”
Section: The Problem With Comparing Single Hr-far Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis reported by Palmer and Brewer (2012) represents an important step forward in that it used signal-detection concepts to clearly separate accuracy-that is, how far an ROC falls above the diagonal line of chance performance-from response biasthat is, where a point falls on an ROC (Ebbesen & Flowe, 2002;Meissner et al, 2005). However, actually performing ROC analysis would be a far better way to investigate this issue because it is not dependent on detailed theoretical assumptions, whereas the analysis reported by Palmer and Brewer is dependent on numerous minimally tested assumptions that eyewitness memory researchers are free to dispute (e.g., the target and lure distributions are assumed to be Gaussian in form and to have the same variance, an integration decision rule is assumed instead of an independent observations decision rule, the decision rule is assumed to be the same for both lineup procedures, etc.).…”
Section: The Problem With Comparing Single Hr-far Pairsmentioning
confidence: 99%
“…In other words, theoretical assumptions are used to estimate from a single HR-FAR pair what the rest of the ROC would look like had the ROC data actually been collected. Using this approach, Palmer and Brewer (2012) recently fit a theoretical signal-detection model to single pairs of hit and false alarm rates produced by simultaneous and sequential lineups in previously published studies. They found that both procedures yield approximately the same d=, from which one might infer that the two procedures would yield approximately equivalent ROCs (contrary to the idea that there is a sequential superiority effect) and that they differ only in that the sequential procedure yields more conservative responding.…”
Section: The Problem With Comparing Single Hr-far Pairsmentioning
confidence: 99%
“…Three decades of such studies have quantified the effects of many of these variables on identification accuracy (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Simply put, data on estimator variables tell us something about the probative value of eyewitness testimony-and thus the degree to which law enforcement and the courts should be circumspect-given the conditions under which a crime was witnessed.…”
Section: Variables That Influence Eyewitness Performancementioning
confidence: 99%
“…The model accounts for all identification decisions: suspect identifications, foil identifications and lineup rejections in both target-present and target-absent lineups. Therefore, the model fitting helps us to understand witnesses' decision-making processes and illustrates how willingness to make identifications (i.e., placement of the decision criterion) changes with differences in discriminability (Palmer & Brewer, 2012 µ innocent distributions and reflect poorer discriminability (see Figure 4).…”
Section: Modelingmentioning
confidence: 99%